De novo mutations in EIF2B1 affecting eIF2 signaling cause neonatal/early onset diabetes and transient hepatic dysfunction - De Franco, Elisa (Diabetes, 2020)
Permanent neonatal diabetes is caused by reduced β-cell number or impaired β-cell function. Understanding the genetic basis of this disorder highlights fundamental β-cell mechanisms. We performed trio genome sequencing for 44 permanent neonatal diabetes patients and their unaffected parents to identify causative de novo variants. Replication studies were performed in 188 patients diagnosed with diabetes before 2 years of age without a genetic diagnosis. EIF2B1 (encoding the eIF2B complex α subunit) was the only gene with novel de novo variants (all missense) in at least three patients. Replication studies identified 2 further patients with de novo EIF2B1 variants. In addition to diabetes, 4/5 patients had hepatitis-like episodes in childhood. The EIF2B1 de novo mutations were found to map to the same protein surface. We propose that these variants render the eIF2B complex insensitive to eIF2 phosphorylation which occurs under stress conditions and triggers expression of stress-response genes. Failure of eIF2B to sense eIF2 phosphorylation likely leads to unregulated unfolded protein response and cell death. Our results establish de novo EIF2B1 mutations as a novel cause of permanent diabetes and liver dysfunction. These findings confirm the importance of cell stress regulation for β-cells and highlight EIF2B1’s fundamental role within this pathway.